Treatment of Acute Hemorroidal Fluxion by Maximum Anal Dilatation.: preliminary communication - Bermúdez, Jorge; Kamaid, Emil (Cirugía del Uruguay, 1980)
Acute hemorroidal fluxion is one of the most frequent and sevePe complications of ·hemorroidal disease. There is no ideal treatment to cure both disease and .complication rapidly, entailing neither risk nor sequela